The effect of plywood thickness on the profiled steel sheeting dry board (PSSDB) floor panel stiffness - Fatin Naimah, Ismail (2014)
Due to the increasing demand of construction in Malaysia, the government has embarked and taken initiative to implement the Industrial Building System (IBS) such as the Profiled Steel Sheeting Dry Board (PSSDB). PPSDB panelling system can be classified as lightweight composite structural system and can be used as a floor, roof and wall panel. This PSSDB system. consists of Steel Sheeting (SS) and Dry Board (DB) which 'is connected to each other with self-tapping and self-drilling screws. PSSDB system can be used as temporary shelter and is suitable because it will reduce the time construction. Besides that, PSSDB system can also reduce the use of the materials like concrete and timber formworks hence reduce the overall cost. The objectives of this research are to determine the stiffness of the floor panel and to identify the relationship between thicknesses of dry board and panel stiffness. In this study, three pieces of 1.0 mm Peva45 and three different thicknesses of Plywood; 12 mm, 18 mm and 20 mm, have been used in the PSSDB floor panel as steel sheeting and dry board respectively. Meanwhile, MK-Fasteners screws type is used to attach the SS and DB together. Through the bending experiment, the stiffness of the panel can be determined by calculating the slope for each graph of Load vs. Deflection that has been obtained. The result shows that the stiffness value is increased from 109 kNm2/m to 122 kNm2/m when the thickness of plywood is increased from 12 mm to 18 mm. Similarly, when the thickness is 20 mm, the stiffness value is increased to 129 kNm2/m. According to the results obtained, it showed that the thicker plywood will give the higher value of stiffness. In other words, the thicker the plywood, the higher the value of stiffness. Therefore, the thickness of the plywood plays the important role in determining the value of stiffness.